Synthesis of Paclitaxel‐Conjugated β‐Cyclodextrin Polyrotaxane and Its Antitumor Activity1. Issue 28 (5th June 2013) - Yu, Shuling; Zhang, Yajun; Wang, Xin; Zhen, Xu; Zhang, Zhaoheng; Wu, Wei; Jiang, Xiqun
<x xml:space="preserve">Abstract</x> Cap it all: A β‐cyclodextrin polyrotaxane was synthesized by using poly(propylene glycol) as the axle and β‐cyclodextrin as the end cap. An antitumor agent, paclitaxel, was conjugated to it. The drug‐conjugated polyrotaxane penetrates deep into tumors, impedes tumor growth, and prolongs the life of tumor‐bearing mice better than Taxol.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>